DITV-LEARNING: uma ferramenta de autoria à criação de objetos digitais de aprendizagem para TV Digital Interativa. - Sousa Neto, Fausto Alves de (2012)
The increasing use of computers in schools has been changing the standard of education in Brazil and enabling teachers to interfere with solutions that make the learning process more participatory and interactive. In this scenario the Digital learning objects (DLO) have been shown to be useful. The DLO construction for web or digital TV involves , well as pedagogical knowledge, specific knowledge of computers making its production time consuming and expensive for educational institutions. The cheapness and speed of development of an ODA are crucial factors for improving educational performance. The objective of this work is to develop an authoring tool called DITV-Learning that makes it possible to prepare for the DLO interactive digital TV (TVDI), by professionals who have little skill in computer science.